Dialogue Context in the Story of Two Women from Lachumanpur - Bishnu Neupane (Interdisciplinary Journal of Management and Social Sciences, 2025)
The present study is related to discourse context analysis. The objective of this study is to analyze the physical and cognitive discourse contexts in the story ‘Lachmunpurka Dui Nari’ collected in Madanmani Dixit’s Shwetakali story collection. Discourse context analysis can be performed for any text. The presented story is also a text. This story presents physical contexts such as place, time, place, participant and social, economic, religious-cultural and ideological cognitive contexts. Therefore, this story is a suitable work to analyze on the basis of discourse context. Therefore, this article analyzes the discourse contexts presented in the story ‘Lachmunpurka Dui Nari’. For the analysis of the presented story, the basic principles of discourse analysis have been adapted and textual analysis has been carried out. Primary and secondary sources have been studied, analyzed and interpreted using the inductive method. Both physical and cognitive contexts are presented in the story. The Lachumanpur village located in the Bara district of the Terai, the well there, Raghubir’s hut, the khatiya in the Osara, the cold hut, the school, the family home and the husband’s home are the spatial contexts. The morning, afternoon, evening, the time of lighting the lamp, the night, etc. of the month of Chaitra indicate the temporal context in the story. The story presented is an incident that occurred during two hours of the evening. Musaharani, Kurmini, Raghubir and Dhanraj indicate the participatory context. The spatial, temporal, temporal and participatory contexts presented also indicate the cognitive context. Under this, they indicate the social, economic, religious-cultural and ideological contexts. It is concluded in this article that the story has become more powerful due to these physical and cognitive contextual contexts presented in the story.